International Branch Campuses: Can They Be Research Universities - Sutrisno, Agustian (International Higher Education, 2018)
International branch campuses are often seen as teaching institutions. There are several factors inhibiting research at these campuses. Three possible scenarios to transform them into more research-intensive institutions are discussed in this article.